Rent indices for housing in West Germany 1985 to 1998 - Johannes Hoffmann; Claudia Kurz (Deutsche Bundesbank, 2002)
In several studies, hedonic methods have been used successfully for the ex post assessment of the accuracy of inflation measurement. Most of those studies relate to high-tech products, with respect to which traditional methods of compiling price indices often fail. We apply hedonic methods to rental housing services, which display less quality progress. However, as German households devote about 10 % of their total expenditure to rented housing services, even a small bias in this field might induce a substantial distortion in overall inflation measurement. On the basis of data from the German Socio-Economic Panel, we perform a hedonic analysis of housing rents and compile different price indices. Overall, we conclude that there is some evidence of an understatement of rent inflation in the official rent index for West Germany at the beginning of the 1990s. – – Hedonische Methoden wurden in einer Reihe von Studien erfolgreich für die ex post Analyse der Genauigkeit der Inflationsmessung verwendet. Die meisten dieser Studien beziehen sich auf High-tech Produkte, bei denen traditionelle Methoden zur Berechnung von Preisindizes oftmals versagen. Wir wenden hedonische Methoden auf Mieten für Wohnungen an. Dort ist der Qualitätsfortschritt weniger stark. Da aber die privaten Haushalte in Deutschland rund 10 % ihres Budgets für Mieten ausgeben, könnte selbst eine kleine Verzerrung in diesem Bereich die Genauigkeit der Inflationsmessung insgesamt empfindlich stören. Auf Grundlage von Daten des Sozioökonomischen Panels schätzen wir hedonische Gleichungen für Wohnungsmieten und berechnen verschiedene Indizes. Insgesamt kommen wir zu dem Ergebnis, dass es in Westdeutschland Anfang der neunziger Jahre Hinweise auf eine Unterschätzung des Mietenanstiegs durch den offiziellen Mietenindex gab.
Keywords: C21; D43; D12; E31; 330; Consumer Price Index; hedonics; housing; matched models; Miete; Lebenshaltungsindex; Index; Hedonischer Preis; Schätzung; Deutschland